Exploratory analysis on the relationship between dietary live microbe intake and arthritis: a national population based cross-sectional study - Liu, Yiping; Xing, Yida; Kong, Xiaodan (Frontiers in Nutrition, 2024)
The pathogenesis of arthritis such as rheumatoid arthritis (RA) and osteoarthritis (OA) remains unclear. This study aims to investigate whether the intake of live dietary microbes can be used as an auxiliary means for the treatment of arthritis.Methods: Data used in the present research were originated from the US National Health and Nutrition Examination Survey (NHANES) from 2003-2018. Participants involved in the present study were categorized into three groups based on the dietary live microbe classification system, namely low, medium, and high dietary live microbe groups. The analyses utilized weighted univariate and multivariate logistic regression. The restricted cubic spline plot was used to explore the relationship between the high dietary live microbe group and the odds of arthritis.Results: 12844 participants were included in the present study. The intake of high live dietary microbes in RA group was lower than that in healthy control group and OA group. The proportion of RA patients in the high live dietary microbe group was lower than that in the low and medium live dietary microbe group. Following the comprehensive adjustment for covariates, it was observed that participants in both the high and medium dietary live microbe groups exhibited lower odds of RA compared to those in the low dietary live microbe group (High OR: 0.71, 95% CI: 0.53-0.96; Medium OR: 0.77, 95% CI: 0.59-1.00, p =0.02). A restricted cubic spline plot indicates a negative correlation between the quantity of dietary live microbes and the occurrence of RA within the high dietary live microbe group.The results of our study revealed a significant difference in dietary live microbe intake between healthy and RA patients. Higher dietary intake was correlated with a decreased odds of RA. However, no significant association was found between the occurrence of OA and the quantity of dietary live microbes.